2015
DOI: 10.1007/s00406-015-0630-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered intrinsic organisation of brain networks implicated in attentional processes in adult attention-deficit/hyperactivity disorder: a resting-state study of attention, default mode and salience network connectivity

Abstract: Deficits in task-related attentional engagement in attention-deficit/hyperactivity disorder (ADHD) have been hypothesized to be due to altered interrelationships between attention, default mode and salience networks. We examined the intrinsic connectivity during rest within and between these networks. Six minutes resting state scans were obtained. Using a network-based approach, connectivity within and between the dorsal and ventral attention, the default mode and the salience networks was compared between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 66 publications
(100 reference statements)
8
56
2
Order By: Relevance
“…Multisensory integration is also known to be disrupted in several developmental disorders including schizophrenia (De Jong et al, 2010; Postmes et al, 2014; Mayer et al, 2015), dyslexia (Facoetti et al, 2010; Krause, 2015), and autism (Ciesielski et al, 1995; Belmonte and Yurgelun-Todd, 2003; Foss-Feig et al, 2010; Kwakye et al, 2011; Woynaroski et al, 2013). In addition, many developmental disorders also have strong links to alterations in attentional networks, executive functioning, and higher-order processes (Cardinale et al, 2013; Kamradt et al, 2014; Sidlauskaite et al, 2016). However, very few studies have examined how the relationship between attention and multisensory integration develops or the link between multisensory integration and attention in developmental disorders and its role in shaping the trajectory, severity, and functioning of individuals with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Multisensory integration is also known to be disrupted in several developmental disorders including schizophrenia (De Jong et al, 2010; Postmes et al, 2014; Mayer et al, 2015), dyslexia (Facoetti et al, 2010; Krause, 2015), and autism (Ciesielski et al, 1995; Belmonte and Yurgelun-Todd, 2003; Foss-Feig et al, 2010; Kwakye et al, 2011; Woynaroski et al, 2013). In addition, many developmental disorders also have strong links to alterations in attentional networks, executive functioning, and higher-order processes (Cardinale et al, 2013; Kamradt et al, 2014; Sidlauskaite et al, 2016). However, very few studies have examined how the relationship between attention and multisensory integration develops or the link between multisensory integration and attention in developmental disorders and its role in shaping the trajectory, severity, and functioning of individuals with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These reports (47;122;143) illustrate the obstacles posed by variations in nomenclature and network boundaries. Encouragement by reviewers and editors to use common frameworks, such as the Yeo-Krienen networks (65), at least for supplementary analyses, would hasten resolution of such ambiguities.…”
Section: Emerging Models Of Brain Functional Organization In Adhdmentioning
confidence: 98%
“…A multi-network SBC examination in adults with ADHD differentiated four: salience, DMN, dorsal and ventral attention (143). The authors found decreased salience to dorsal attention network FC in ADHD, whereas dorsal and ventral inter-network FC was increased (143).…”
Section: Emerging Models Of Brain Functional Organization In Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a resting-state fMRI study in patients with ADHD and healthy controls, Sidlauskaite et al [6] investigated connectivity between brain regions involved in these circuits. In ADHD, hyperconnectivity was detected between attention networks and within the default and ventral attention network.…”
mentioning
confidence: 99%